PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DALAM PEMBELAJARAN DARING TERHADAP MOTIVASI BELAJAR SISWA SMK PERPAJAKAN RIAU - Nurul Fadhilah; Zilan Zailila; Jamalia Oktavia; Citra Wulandari; Intan Suri (STKIP Pesisir Selatan, 2022)
The purpose of this research is to increase students' motivation in participating in the Japanese class of XII grade students of SMK Perpajakan Riau. The material used in this study was a video learning material chapter 3 about self-introduction or Hajimemashite from the Sakura textbook used by Japanese language teachers for teaching. The method used in this research is quantitative research with data collection techniques using a absence via google glassroom. Based on the results of data management, data observation and data analysis, it can be seen that the effect of learning using learning media in the form of PowerPoint and video is more effective. This effectiveness can be used as an indicator of the learning process that uses learning media to further increase student motivation to attend class better than the learning commonly used by teachers in these schools. Researchers hope that this research can improve the online learning methods used by teachers so that they can attract student interest and motivation in online learning so that students will be interested and diligent in participating in learning without feeling bored with the material provided by the teacher in the future, especially during this covid-19 pandemic